O desenvolvimento brasileiro e o Sistema Interamericano de Direitos Humanos: uma análise da situação dos soldados da borracha no Brasil - Oliveira Junior, Alberto Lopes de (2013)
It is a legal research focused on the study of socio, political and economic development of Brazil. The development towards treated in this work has direct relation to the evolution of the people, in an inclusive and fraternal, enabling all, without exception, the right to participation and enjoyment of the product of this development. Development here is exposed as a complex network formed by another complex elements, which, when united, form a system. This system should protect economic growth, ensuring social and political evolution. The Inter-American System of Human Rights is considered as a complementary channel to the Brazilian legal system, available to citizens, to guarantee and protect human rights, which is a presupposition to the development. As an experiment for the application of the Inter-American System of Human Rights in Brazil's development, we will analyze the situation of the Rubber Soldiers, lived in northern of the Brazil. Rubber Soldiers were men recruited in the opportunity of the Government of Getúlio Vargas, as the Allied war effort, the United States, at the time of the second world war. These men left their lands in the Northeast and were induced to move their lives to the north of the country, hoping to aid the motherland and better quality of life. However, they were treated as slaves and never received any honors as Soldiers. Treatment that differentiates them from "Excombatants", a class that had been treated as a priori similar. The reasoning method and approach of this work is outlined by means of induction (inductive), which analyzes data from a particular case to verify a general reality. It is a systematic analytical study